Prosopanche cocuccii (Hydnoraceae): a new species from Southern Brazil - de Carvalho, Jordano D. Tavares; Markus, Catarine; Junior, Aldo Merotto; Záchia, Renato A.; Schuch, Marilia; Sulzbach, Estéfani; Mariath, Jorge E. A. (Phytotaxa, 2021)
Prosopanche cocuccii is described as a new species from Southern Brazil. It resembles P. bonacinae due to the trigonous rhizome and by the general size of the flower organs. Nevertheless, P. cocuccii is distinguished by the main floral morphological characteristics used to differentiate species. In addition, the new species presents some rare characters for the genus, such as a highly branched rhizome and flowers usually grouped in fascicles. We provide a description, illustrations, field photographs, morphological details under the stereomicroscope, and comments on habitat, ecology, distribution, and conservation of the new species, as well as an updated key for the genus Prosopanche. In addition, we identified that P. cocuccii produces a large number of rhizomes and fruits for each single host specimen of tobacco (Nicotiana tabacum), which resulted in a decrease in height and growth of its only known host plant.